Update: advanced methods in three‐dimensional organotypic tissue engineering for congenital ichthyosis and other rare keratinization disorders. (December 2014) - Eckl, K.M.
<x xml:space="preserve">Abstract</x> ORIGINAL ARTICLE, p 1347